HUBUNGANANTENATAL CARE (ANC) DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI KABUPATEN WONOSOBO - , Rahmat Haji Saeni ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The prevalence of LBW is different from one to other regions in Indonesia, the rate between 9%-30%. In 2007, the percentage of LBW in Central Java was 2.26% but in 2008 was 2.08%. The amount of cases of LBW in Wonosobo District in 2008 were 17 cases , in 2009 were 29 cases and in 2010 were 33 cases per 1000 live births. Early detection of fetal health and abnormalities can be done by prenatal check up regularly named antenatal care (ANC). In 2008, coverage of first visitation of pregnant women (K1) in Wonosobo District was 93.04% and in 2009 was 97.58%. The coverage of fourth visitation of pregnant women (K4) in 2008 was 85.62% and in 2009 was 90.45%. Objective:. To determine the relationship between ANC and LBW Method:. This was an observational study with case control design. The population was all mothers who gave birth and recorded in the register of primary health care in 2010. The case group was mothers who delivered LBW and the control group was mothers who did not deliver LBW. Sampling technique was simple random sampling. Result: Bivariate analysis showed that the pregnant woman who had ANC inadequate status has a risk 1.15(CI 95% 0.71-1.90). Whereas the pregnant woman who had irregularly ANC status has a risk 2.33 (CI 95% 1.47-3.69). Conclusion:. The pregnant woman who had ANC inadequate status has a risk 1.15 times and the pregnant woman who had irregularly ANC status has a risk 2.33 times to birth LBW